Generation of nanobodies against the F protein of respiratory syncytial virus and establishment of an indirect immunofluorescence assay - Qianqian Wang; Dongxiang Hong; Entao Li; Zekai Cheng; Jiachen Zhang; Tengchuan Jin; Sandra Chiu (Microbiology Spectrum)
ABSTRACT Respiratory syncytial virus (RSV) infection is a leading cause of acute respiratory infections and death in children and older adults. Currently, there is a lack of effective vaccines and antibody treatments on the market, and the clinical manifestations of RSV are indistinguishable from those of acute respiratory infections caused by other etiologies. Therefore, the prevention and treatment of RSV require not only effective vaccines but also simple, fast, cost-effective, and accurate detection and diagnostic methods. Given the small molecular weight, excellent antigen-binding specificity, and affinity of nanobodies, we successfully obtained a panel of nanobodies by expressing the RSV F protein, immunizing camel, and establishing a phage display library. Among them, F-E2 has been shown to bind specifically to the RSV F protein and can be used for Western blot, enzyme-linked immunosorbent assay, flow cytometry, immunohistochemistry, and immunofluorescence assays. Moreover, an RSV immunofluorescence detection method based on F-E2 has been established and proved to be highly specific, sensitive, cost-effective, and fast, with great application potential.IMPORTANCEA respiratory syncytial virus (RSV) detection nanobody, F-E2, was successfully screened by constructing a dromedary camel immune library. F-E2 binds to RSV F with ng affinities and can be used for Western blot, enzyme-linked immunosorbent assay, flow cytometry, immunohistochemistry, and immunofluorescence assays. Importantly, a high-throughput RSV immunofluorescence detection method based on F-E2 has been established and proved to be highly specific, sensitive, cost-effective, and fast, with great application potential.